Relative and incremental value relevance of equity and earnings in the Nigerian financial industry after mandatory Adoption of International Financial Reporting Standard (IFRS) - Bagudo, Muhammad Mustapha; Abdul Manaf, Kamarul Bahrain; Ishak, Rokiah (American Scientific Publishers, 2015)
The study examines the relative and incremental value relevance of mandatory adoption of IFRS in the Nigerian financial industry using Ohlson (1995) model.Data is collected from 52 companies for the period 2010–2013. The overall result shows that the adoption of IFRS improved the value relevance of accounting information in the Nigerian financial industry.The Book Value per Share (BVPS) and Earnings per Share (EPS) are higher under IFRS than under SAS. The combined value relevance measured by adjusted R2 is also higher under IFRS.The study contributes to the value relevance literature in Africa.